2010
DOI: 10.1172/jci40364
|View full text |Cite
|
Sign up to set email alerts
|

Stat3-dependent acute Rantes production in vascular smooth muscle cells modulates inflammation following arterial injury in mice

Abstract: Inflammation is a key component of arterial injury, with VSMC proliferation and neointimal formation serving as the final outcomes of this process. However, the acute events transpiring immediately after arterial injury that establish the blueprint for this inflammatory program are largely unknown. We therefore studied these events in mice and found that immediately following arterial injury, medial VSMCs upregulated Rantes in an acute manner dependent on Stat3 and NF-κB (p65 subunit). This led to early T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 68 publications
6
92
0
2
Order By: Relevance
“…Our data also indicated that STAT3 contributed to RANTES overexpression in TRM-7 cells. Inhibition of STAT3 phosphorylation led to downregulation of RANTES mRNA levels (40). This was supported by the observation that STAT3 regulated RANTES promoter activity in MCF-7 cells.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Our data also indicated that STAT3 contributed to RANTES overexpression in TRM-7 cells. Inhibition of STAT3 phosphorylation led to downregulation of RANTES mRNA levels (40). This was supported by the observation that STAT3 regulated RANTES promoter activity in MCF-7 cells.…”
Section: Discussionmentioning
confidence: 67%
“…Phosphorylated STAT3 upregulates RANTES expression RANTES is a STAT3 target gene (40,41). To investigate the role of STAT3 activation in RANTES expression, we used the JAK2 inhibitor, AG490, which suppresses constitutive STAT3 activation.…”
Section: Rantes-mediated Stat3 Activationmentioning
confidence: 99%
“…Open Biosystems TC1 library numbers TCRN0000071453 to TCRN0000071457 were used (pLKO.1 vector). 33 Control shRNA virus SHC-002 (SigmaAldrich) was used to create a stable control knockdown line. Cells were maintained in selection media containing 2 g/mL puromycin, to which the lentiviral vectors conferred resistance but completely killed uninfected cells.…”
Section: Shrna Knockdownmentioning
confidence: 99%
“…RANTES induces the chemotaxis of multiple immune cells (17) and is secreted by many cell types including fibroblasts (18), epithelial cells (19), and vascular smooth muscle cells (20). High levels of RANTES are associated with several pathologies including atherosclerosis (21), various cancers (22,23), diabetes (24), glomerulonephritis (25), and rheumatoid arthritis (26).…”
mentioning
confidence: 99%